EVALUATION OF HYDROGEL MASK PREPARATION OF RED MANGROVE LEAF ETHANOL EXTRACT (Sonneratia caseolaris Engl.) - Sa’diyah, Aminatus; Pambudi, Dwi Bagus (Universitas Pekalongan, 2024)
Hydrogel preparations are preparations that have a fairly high water content, ranging from 80-90%. Sonneratia caseolaris Engl is a type of mangrove plant, locally this tree is often called kapidada. Ecologically, kapidada grows in the less salty parts of the mangrove forest. This study aims to find out whether the red pidada mangrove leaf extract can be formulated into a hydrogel mask preparation. The test method used is a hydrogel mask made by mixing the basic ingredients of the mask in the form of carbopol 940 and TEA. The results of the evaluation test were in the form of an organoleptic test with greenish clear color parameters, odorless, with a thick gel form. The resulting pH test was formula 1 with a pH value of 5, formula 2 with a pH value of 6 and formula 3 with a pH value of 5. Test the homogeneity of all preparations from the three homogeneous formulas. The spreadability test produced from formula 1 was 5.1 cm, formula 2 was 4.9 cm and formula 3 was 3.6 cm. The adhesion test resulting from the three formulas obtained a value of 1.16; 1.52; and 1.63 seconds. Viscosity test obtained from the three formulas, namely 3,967; 2,989; and 1,737 cps. The results showed that the hydrogel mask preparations met the evaluation requirements, namely formula 1.